PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN KARYAWAN CV MONANG CITA ABADI - Simarmata, Ricardo Manarintar (Jurnal Manajemen & Bisnis Jayakarta, 2023)
Many employees often leave CV Monang Cita Abadi without clear reasons, and some employees who stay do not work optimally, causing work not to be completed on time. This study aims to examine and analyze the impact of job satisfaction on the level of employee commitment at CV Monang Cita Abadi. Data collection methods in this study include the use of questionnaires, interviews, and documentation studies. Furthermore, the data was processed using SPSS 21.0 for windows software. The data analysis method used is descriptive method and Simple Linear Regression to measure the effect of Job Satisfaction (X) on Employee Commitment at CV Monang Cita Abadi. The results of testing the correlation coefficient (R) show that the relationship between job satisfaction and employee commitment is very close. Job Satisfaction is proven to be the dominant factor influencing Employee Commitment at CV Monang Cita Abadi.